2020
DOI: 10.1099/mgen.0.000427
|View full text |Cite
|
Sign up to set email alerts
|

Dual transcriptome analysis reveals differential gene expression modulation influenced by Leishmania arginase and host genetic background

Abstract: The outcome of Leishmania infection is strongly influenced by the host’s genetic background. BALB/c mice are susceptible to Leishmania infection, while C57BL/6 mice show discrete resistance. Central to the fate of the infection is the availability of l-arginine and the related metabolic processes in the host and parasite. Depending on l-arginine availability, nitric oxide synthase 2 (NOS2) of the host cell produces nitric oxide (NO) controlling the parasite growth. On the other hand, Leishmania can also use ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 77 publications
(112 reference statements)
0
11
1
1
Order By: Relevance
“…It also decreases putrescine, proline, ornithine, glutamic acid, S-adenosylmethionine, cystathionine, and N-carbamylarginine levels (Table 1 and Figure 6). Despite that, in a previous study, we did not find a modulation of the transcript levels involved in these metabolic pathways in the L. amazonensis infection context, comparing macrophages infected with La-WT and La-arg − [50].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It also decreases putrescine, proline, ornithine, glutamic acid, S-adenosylmethionine, cystathionine, and N-carbamylarginine levels (Table 1 and Figure 6). Despite that, in a previous study, we did not find a modulation of the transcript levels involved in these metabolic pathways in the L. amazonensis infection context, comparing macrophages infected with La-WT and La-arg − [50].…”
Section: Discussioncontrasting
confidence: 99%
“…L. amazonensis infection of BALB/c-macrophages increases host Cat2 and Arg1 transcripts, parasite arginine transporter (amino acid permease 3, AAP3), and parasite arginase [23]. Despite this, C57BL/6-macrophages infected with L. amazonensis did not modulate those genes [28,50].…”
Section: Discussionmentioning
confidence: 94%
“…It is well-known that L-arginine metabolism contributes to macrophage polarization to the M1 or M2 phenotype. We have already demonstrated that macrophage infection with L. amazonensis promotes alterations to this scenario, leading to an M2-like macrophage phenotype in the early stages of infection [34]. To understand the impact of miRNAs on L-arginine metabolism in C57BL/6 macrophages, we focused on the analysis of transcript levels of two arginine transporters (Slc7a1 and Slc7a2-Cationic Amino Acids 1 and 2, respectively), Arginases 1 and 2 (Arg1 and Arg2), Nitric Oxide Synthase 2 (Nos2), and Ornithine Decarboxylase 1 (Odc1).…”
Section: Mir-294-3p Mir-301b-3p and Mir-410-3p Target The L-arginine ...mentioning
confidence: 92%
“…Nitric oxide (NO) production is a defense mechanism used by macrophages being produced by nitric oxide synthase 2 (NOS2) in the presence of the amino acid L-arginine as substrate (Cunningham, 2002). Arginase on the other hand, reduces NO production by limiting the availability of L-arginine and favoring the survival of Leishmania in the macrophage (Camargo et al, 1978;Aoki et al, 2020). Aoki et al (2017) studied gene expression differences between L. amazonensis wildtype (La-WT) and L. amazonensis arginase knockout (Laarg − ) promastigotes and axenic amastigotes.…”
Section: Assessment Of Metabolic Pathwaysmentioning
confidence: 99%
“…Arginase was found to upregulate membrane markers that affect parasite recognition, autophagy-related genes implicated in parasite differentiation and amastins that impact amastigote replication and survival, while modulating oxidative-stress related genes ( Aoki et al, 2019 ). The parasite’s arginase activity also appeared to modulate gene expression in the host macrophage including in the immune response and amino acid transport and metabolism ( Aoki et al, 2020 ).…”
Section: Assessment Of Metabolic Pathwaysmentioning
confidence: 99%